Direct observation of a-b twin laminate in monoclinic five-layered martensite of Ni-Mn-Ga magnetic shape memory single crystal. (1st April 2017) - Heczko, Oleg; Klimša, Ladislav; Kopeček, Jaromír
Abstract: Full hierarchy of twinning including a-b twin laminate was directly observed by optical and scanning electron microscopy (SEM) in the vicinity of macroscopic, mobile a-c twin boundary in five-layered monoclinic (10M) martensite of Ni50 Mn28 Ga22 single crystals exhibiting magnetically induced reorientation (MIR). The submicron a-b twin laminate was identified by backscattered electrons in SEM. The a-b laminate terminated straight on Type I and by laminate branching on Type II twin boundary in agreement with the model. Graphical abstract: